ANALISIS EFISIENSI BELANJA DAERAH DI PROVINSI JAWA BARAT PADA ANGGARAN BIDANG PENDIDIKAN DAN KESEHATAN TAHUN 2009 - 2013 - Muhammad Angga Wicaksono (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study analyze the cost efficiency and system efficiency of public spending in 10 district/cities in West Java province, especially education and health spending. The study uses the data on period 2009 – 2013 and used Data Envelopment Analysis (DEA). Variables used to see the efficiency in the field of education is education spending as input variables, student-teacher ratio and school-student ratio as intermediate output variable and Literacy Rate and Average Length of School as output variables. While the variables used to see the efficiency in the health sector is helath spending as input variables, health worker/capita ratio and puskesmas(health centre)/capita ratio as intermediate output variables and Life Expectacy as output variables. Based on calculations by the DEA shows that the efficiency score on average in the five year have not been efficient. The city of Bandung is able to achieve overall efficiency in all years of study in the field of education. For the health sector, none of the area is able to achieve overall efficiency throughout the study. Inefficiencies in other areas shows that the resource allocation system is bad because of weak government management system  Key Words : Efficiency, public spending, Data Envelopment Analysis (DEA)